Implementasi Data Mining Untuk Bantuan Dana Bansos Dengan Menggunakan Algoritma C4.5 Di Pemerintahan Kabupaten Empat Lawang - Pahmi Ladianto (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
The Empat Lawang Regency Government in advancing the welfare of its people has a program in the form of social assistance. The Empat Lawang Regency Government in distributing social assistance in the form of demolition of uninhabitable houses. Because in Empat Lawang Regency, there are still many people below the eligibility line, including housing or houses that are not suitable for habitation. While the process to get the house difference starts from the lowest government, namely the Village Head to record the residents who have uninhabitable houses and the economic income per day in meeting the needs of life, then the data is submitted to the Empat Lawang Regency Government. The Verification Team appointed by the Empat Lawang Regency Government made a selection to determine who would receive the social assistance funds. In this study to collect the data needed the author will use the data that has been collected by the Empat Empat Lawang Regency Government regarding the object that will receive assistance, if you have made observations, the author will enter the data into categories and regulations according to the provisions stipulated in the Ministerial Regulation. PUPR Number 13/PRT/M/2016. Next, to filter the data that has been obtained, the author will use System. The system to be built is a web-based system that will be combined with the C4.5 Algorithm.